Symptoms of unknown origin : a medical odyssey - Meador, Clifton K., 1931-2021 (Vanderbilt University Press, 2005)
A doctor's fascinating encounters with "nondisease" and how physicians can recognize and treat patients with symptoms that might at first appear imaginary.